1989
DOI: 10.1002/1520-6629(198910)17:4<356::aid-jcop2290170408>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Identifying variables predictive of success: The next step in alternatives to psychiatric hospitalization research

Abstract: This investigation addresses two issues central to psychiatric hospitalization: (1) Can alternative treatments be effective? and (2) How can patients appropriate for the alternatives be identified? This random design study found that a majority of patients assessed as requiring immediate psychiatric hospitalization could utilize a combination of emergency housing and outpatient treatment to avoid hospitalization. Five key variables examined at intake proved useful in predicting ability to succeed in the altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Both programs were also effective in helping to stabilize permanent housing and income supports. Similarly, Sheridan and associates (1988) found that two-thirds of all clients referred for hospitalization could be served successfully in a special 17-bed unit at the YMCA.…”
Section: Crisis Response Servicesmentioning
confidence: 95%
“…Both programs were also effective in helping to stabilize permanent housing and income supports. Similarly, Sheridan and associates (1988) found that two-thirds of all clients referred for hospitalization could be served successfully in a special 17-bed unit at the YMCA.…”
Section: Crisis Response Servicesmentioning
confidence: 95%
“…Another logical step is the analysis of differential outcomes (19,20), with the aim of determining which persons experiencing an acute psychiatric cri-sis are best treated in a hospital alternative and which are best treated in a hospital setting.…”
Section: Future Researchmentioning
confidence: 99%
“…Based on this testimony, five initial principles for the development of community crisis options emerged: (1) whenever possible, people should be provided with the supports they need to resolve a crisis without being removed from familiar surroundings; (2) if people prefer to leave their homes during a crisis (or if they have no home), safe, non-threatening, non-hospital settings should be available; (3) a wide range of voluntary treatment and support options should be available in all settings; (4) emphasis should be placed on developing natural and peer supports; and (5) effective communication networks should be developed so that all people have a way to let others know when they are approaching crisis. Recent literature on community crisis alternatives support the validity of these principles (Bond et al, 1987; Sheridan, Zuskar, Walsh, & O'Brien, 1987; Stroul, 1987; Weisman, 1985).…”
Section: The Vermont Regionalization Projectmentioning
confidence: 98%